An examination from 1990 to 2019: investigating the burden of knee dislocation on a global scale - Chen, Cheng; Li, Bing; Zhou, Haichao; Ye, Tianbao; Yang, Yunfeng (Frontiers in Public Health, 2024)
The literature on the disease burden of knee dislocation is lacking. The aim of the study is to systematically assess the global burden, trends, causes, and influencing factors of knee dislocation.The incidence and years lived with disability (YLDs) of knee dislocation were assessed globally, as well as at the regional and national levels from 1990 to 2019.Subsequent analyses focused on the age and gender distribution related to knee dislocation. An investigation into the main causes of knee dislocation followed. Finally, the Pearson correlation between age-standardized rates and social-demographic index (SDI) was calculated.Results: Although the age-standardized incidence and YLDs rate of knee dislocation decreased over the past thirty years, the incidence and YLDs number increased. The disease burden remained higher in males compared to females. Males and females showed different patterns of incidence rates in each age group, but their YLDs rates were similar. Over the past thirty years, the disease burden of knee dislocation increased in the elderly while declining in the younger population. Falls had consistently emerged as the most important cause for both incidence and YLD rates. Additionally, a positive correlation between SDI and the disease burden of knee dislocation was found.The disease burden of knee dislocation remains heavy. It is essential to recognize the evolving epidemiology of knee dislocation. Utilizing data-driven assessments can assist in formulating public health policies and strategies to improve overall well-being.